Synthesis of α, β‐Unsaturated δ‐Lactones by Vinyl Acetate Mediated Asymmetric Cross‐Aldol Reaction of Acetaldehyde: Mechanistic Insights. Issue 24 (15th July 2014) - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali
Abstract: A tandem asymmetric cross‐aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric β‐hydroxy aldehydes. By using this methodology we have accessed α, β‐unstaurated δ‐lactones as well as isochromenones with high enantioselectivities from both asymmetric β‐hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross‐aldol reaction of acetaldehyde and in the key cis / trans isomerisation step in the synthesis of δ‐lactones. Abstract : A tandem asymmetric cross‐aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate provides access to α, β‐unsaturated δ‐lactones as well as isochromenones with high enantioselectivities. DFT studies were performed to gain mechanistic insights into the reaction.